INTEGRAÇÃO DO BIM AO PLANEJAMENTO URBANO (REMUNOM, 2024)
Information technologies are becoming increasingly pervasive and their utilization along with the availability of GIS data facilitates the development of software incorporating the concept of CIM, which are essential tools for creating smart cities. This study aimed to explore the scientific research on the integration of BIM into urban planning for the development of smart cities. For that, both quantitative and qualitative analyses were conducted, involving the tabulation of numerical data and content collected and diagnosed.The research showed a significant diversity of approaches, such as case studies, literature reviews, theoretical frameworks with innovative and sustainable models, among others. Regarding the temporality, there was an increase in the number of published articles on the topics, with the year of 2022 being the year the highest number of publications. This increase is linked to the creation of events and documents, such as the Brazilian Charter for Smart Cities of 2021, which have a crucial role in promoting scientific research on the integration of BIM into urban planning, in which its results become the basis for public managers' decision-making, aiming to enhance urban efficiency, quality of life and vibrancy in cities.